Tree Wardens and public grounds management in North America: Overseeding athletic fields with perennial ryegrass to promote safe playing surface. Issue 4 (1st October 2016) - Harper, Richard W.; Autio, Wesley R.; Finn, John T.; Rossi, Frank S.
Abstract : Responsibilities of the municipal/urban forester, or Tree Warden as the position is known in parts of the United States, may extend to a variety of widely used community green spaces that include gardens, landscapes and athletic fields. In recent years, the application of non-chemical, cultural methods pertaining to the management of publically accessible athletic fields has garnered growing interest. This is especially true as it relates to weed control and the maintenance of desirable turfgrass cover and safe playing conditions. Based on previous research, a demonstration field study was conducted over four growing seasons (2005–2008) to determine the effectiveness of weekly, repetitive (8×), late summer – early fall overseeding with varying rates of perennial ryegrass: 0, 1, 3 and 6 lbs 1000 ft −2 . Overseeding at the highest rate (6 lbs 1000 ft −2 ) appeared to generate the greatest increase in desirable turfgrass cover during growing seasons that received adequate, well-distributed rainfall. The relationships between amenity and sports grass management and adjacent trees are considered.